Competence-Based Public Relation in Higher Education - Ipung Sri Purwanti Hery (Common Publisher, 2019)
Entering the era of campus autonomy, almost all tertiary education institutions are faced with a situation of readiness for independent funding, quality educational services and healthy competition among other universities. These prerequisites are non-negotiable, however, the image of higher education institutions to be respected must also be considered by all parties so that the impression of cheap competition does not penetrate the institutions that produce our intellectual cadres. What strategic efforts are made that higher education institutions do not get caught up in cheap business strategies and mislead their young generation? It is noteworthy that before the era of campus autonomy was rolled out actually higher education institutions, both State Universities and Private Universities, were already in a public space filled with management demands that prioritize openness and professionalism. Students as consumers, education services are consumers who have critical, rational and responsive characteristics so that the management of higher education should be handled in an integrated manner. The repressive era has passed, but the anarchism era on campus should not spread. For those who have been aware of this reality, the era of campus autonomy is more of an affirmation of policies that are more oriented towards building credibility or institutional or Corporate Identity which is oriented towards Good Corporate Governance. Large private universities in Yogyakarta or Solo do not seem to have experienced panic. Meanwhile, for state universities that rely on funds from the central government, some are starting to lose ground, especially for private universities whose policies are still oriented towards being inward looking and just being able to live. The author agrees that society needs to be more vigilant. Because there will definitely be higher education institutions that will blindly respond to the competition map going forward. Ethics in selling their products can be full of